2011
DOI: 10.1002/jms.1984
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric characterization of peptides containing different oxidized tryptophan residues

Abstract: The term reactive oxygen species refers to small molecules that can oxidize, for example, nearby proteins, especially cysteine, methionine, tryptophan, and tyrosine residues. Tryptophan oxidation is always irreversible in the cell and can yield several oxidation products, such as 5-hydroxy-tryptophan (5-HTP), oxindolylalanine (Oia), kynurenine (Kyn), and N-formyl-kynurenine (NFK). Because of the severe effects that oxidized tryptophan residues can have on proteins, there is a great need to develop generally ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…ApoA1 containing a 2-OH-W72 group is abundant in atherosclerosis-laden arteries and could predict CHD risk [9]. Here we found that MPO-catalyzed nitration and chlorination also results in the oxidation of W72 to form the singly oxidized product, W + O (16 Da), doubly oxidized product, W + 2O (32 Da), and the oxidation of W to kynurenine [30] (W + 4 Da) (Fig. 1).…”
Section: Resultsmentioning
confidence: 84%
“…ApoA1 containing a 2-OH-W72 group is abundant in atherosclerosis-laden arteries and could predict CHD risk [9]. Here we found that MPO-catalyzed nitration and chlorination also results in the oxidation of W72 to form the singly oxidized product, W + O (16 Da), doubly oxidized product, W + 2O (32 Da), and the oxidation of W to kynurenine [30] (W + 4 Da) (Fig. 1).…”
Section: Resultsmentioning
confidence: 84%
“…A number of state-of-the-art techniques, such as the reverse-phase high-performance liquid chromatography (RP-HPLC) combined with UV and fluorescence detection (Simat and Steinhart 1998;Simat et al 1994) or mass spectrometry (MS) ( Van de Weert et al 1998;Dominques et al 2003;Szuchman-Sapir et al 2008;Mouls et al 2009), are available for efficient analysis of tryptophan oxidation products. In fact, oxidized tryptophan residues, such as 5-HTP, Oia, NFK, and Kyn, have been reported to exhibit different fragmentation characteristics in both MALDIand ESI-tandem MS that in turn help in their identification by specific marker ions, in addition to their increment masses within a given ion series (Todorovski et al 2011). Todorovski et al (2011 were able to distinguish the isomeric 5-HTP-and Oiacontaining peptides.…”
Section: Overviewmentioning
confidence: 98%
“…Tyrosine and tryptophan are among amino acids that are most prone to ROS-mediated irreversible oxidation (Berlett and Stadtman 1997;Davies 2003;Stadtman and Levine 2003;Todorovski et al 2011). Indole ring is the normal target of the ROS attack on tryptophan, where 5-hydroxy-tryptophan (5-HTP), oxindolylalanine (Oia), dioxindolylalanine, N-formylkynurenine (NFK), kynurenine (Kyn), hydroxykynurenine, and hydroxy-N-formyl-kynurenine are produced as the tryptophanoxidation products (Simat and Steinhart 1998;Garrison 1987).…”
Section: Overviewmentioning
confidence: 99%
“…Several of these modified proteins include actin, troponin, H-FABP, and complex V. However, due to the multiple isomeric oxidative degradation products (e.g., serotonin or 5-hydroxytryptamine and oxyindolylalanine) that occur, it has been difficult to distinguish these in a complex protein mixture. Hoffman and colleagues (280) have shown that by using high-energy ESI-CID with isolated peptides, the differences in masses within a given ion series and specific marker ions could differentiate the isomeric forms of 5-HT and oxindolylalanine. This suggests that in complex protein mixtures, the possibility of identifying these isomeric forms is feasible.…”
Section: Tryptophanmentioning
confidence: 99%